Neurology Morbidity and Mortality Conferences and Quality Improvement: Single-Center Experience and National Survey. (April 2022) - Ryan, Sophia L.; McKee, Kathleen E.; Londono-Sanchez, Lizbeth; Dougherty, Sarah; Singhal, Aneesh B.
Background: Morbidity and Mortality (M&M) conferences are widespread but vary in goals and methodology. Some focus on clinical enigmas while an increasing number utilize quality improvement (QI) tools to effect systems change. Little is known about the current state of US Neurology M&Ms. Methods: We surveyed 56 US academic neurology departments regarding their M&Ms to understand the use of QI tools and assess variability. Additionally, we reviewed the evolution of M&Ms in our department. Results: The survey was completed by 44 (80%) departments; 68% reported quarterly frequency with 61% discussing 1–2 safety events per conference. The number of written guidelines or protocols resulting from M&Ms in 2 years varied from 0 (14% of departments), 1–2 (45%), to >5 (5%). Institutional culture regarding quality and safety and conference timing were cited by 71% as important in improving participation. In our own department, the M&M format changed in 2014 based on a sentinel patient event combined with improving safety culture across the hospital: neurology M&Ms transformed into thematic quarterly conferences utilizing QI tools. Attendance increased 3-fold, and in 7 years, we have generated 26 guidelines or pathways with corresponding decision-support tools, among other improvement efforts, resulting in specific systems changes. Based on survey results and our experience, suggested M&M "best practices" include the use of just culture, peer review protection, safety event analysis with QI methodology, trainee involvement, and logistical optimization. Conclusion: Structured M&Ms incorporating suggested QI-informed "best practices" can be highly effective in driving system change within neurology.